Impact of Simulation-Based and Flipped Classroom Learning on Self-Perceived Clinical Skills Compared to Traditional Training - Samuel Agostino; Gian Maria Cherasco; Grazia Papotti; Alberto Milan; Federico Abate Daga; Massimiliano Abate Daga; Franco Veglio (Education Sciences)
Introduction: Traditional medical education often emphasises theory, but clinical competence relies greatly on practical, hands-on skills. This quasi-experimental study examines how a combined approach—flipped classroom learning and simulation-based internships—affects medical students’ self-assessed clinical abilities. This model seeks to build students’ understanding, practical skills, and confidence in clinical settings through online preparation and realistic simulation exercises. Methods: This study examined changes in medical students’ self-perceived clinical skills after a flipped classroom and simulation-based internship. A total of 391 third- and fourth-year students completed a nine-hour program with morning practice sessions and afternoon high-fidelity scenarios. Surveys before and after the program assessed self-perceived thoracic and abdominal/general skills. ANCOVA controlled for baseline scores, and paired Wilcoxon signed-rank tests examined overall and subgroup improvements. Results: After the program, significant improvements were observed in self-perceived clinical skills across all domains. Thoracic skills increased from a median of 2.19 to 7.36, and abdominal skills from 5.11 to 9.46. Medical history, vital signs, and blood pressure scores also improved significantly. Third-year students and those attending the Clinical Methodology course showed the greatest gains. All post-intervention improvements were statistically significant (p < 0.001). Conclusions: The combination of flipped classroom learning and intensive simulation training markedly improved students’ perceived clinical competence. These findings suggest that such methods boost students’ practical skills and confidence. Further research is recommended to explore the long-term impact of this approach on skill retention and professional practice.